Kajian Implementasi Rencana Mutu Kontrak pada Proyek Irigasi Berdasarkan Metode Analisis Deskriptif - Paramitha, Thifal Ayu; Usman, Kristianto; Siregar, Amril Maruf (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
Project quality management is a process to keep the project still fulfilled the quality level based on the demand or plan. Quality Plan Agreement is Quality Management System document that is very important in construction project. This research’s aims are to assess the quality implementation level based on Descriptive Analysis Method on Upgrading Irigation Area Project Way Sekampung, Ground Sub-Job. Primary data is obtained by providing questionnaries within 39 questions to 8 respondents and secondary data is obtained by observation and documentation in project site. Descriptive Analysis obtaining 51,28% respondents answer Good; 27,56% respondents answer Very Good; 16,67% respondents answer Acceptable; 4,17% respondents answer Not Good; and 0,32% respondents answer Very Not Good.